تعليم اللغة العربية في المعهد الإسلامي بفونوروغو - Moh Munir (Universitas Yudharta Pasuruan, 2019)
Learning Arabic in Indonesia has experienced the ups and downs along with the dynamics of education in Islamic educational institutions. It gives good attention in Arabic teaching is Islamic boarding school. The Islamic boarding school students have not been able to master language skills well, like Arrisalah concerns with speaking skill and Al amin Hudatul Muna 1 concerns with reading skill. This research focused on three aspects: the materials, the instrutions process and the kinds of languages activities in Arabic teaching in modern and salaf Islamic boarding school for class two. It is kind of qualitative study design to describe the results and collecting the data.The results of this study are: (1) the Arabic teaching materials in modern Islamic boarding school consist of 7 subjects, and salaf consist of 5 subjects. (2) the instructional method in modern Islamic boarding school are used grammar translation method, direct method, audio lingual method, reading method and inductive method. The instructional method in salaf islamic boarding school are used grammar translation method and deductive method. (3) the kinds of language activities in modern Islamic boarding school devided into two kinds namely language activities inside the class and language activities outside the class.